2018
DOI: 10.3390/md16100369
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropane-Containing Fatty Acids from the Marine Bacterium Labrenzia sp. 011 with Antimicrobial and GPR84 Activity

Abstract: Bacteria of the family Rhodobacteraceae are widespread in marine environments and known to colonize surfaces, such as those of e.g., oysters and shells. The marine bacterium Labrenzia sp. 011 is here investigated and it was found to produce two cyclopropane-containing medium-chain fatty acids (1, 2), which inhibit the growth of a range of bacteria and fungi, most effectively that of a causative agent of Roseovarius oyster disease (ROD), Pseudoroseovarius crassostreae DSM 16950. Additionally, compound 2 acts as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 63 publications
1
22
0
1
Order By: Relevance
“…This is an exciting avenue to exploit for potential therapeutics (Kenakin, 2018), and the chemokine receptors are examples of immune-expressed GPCRs with multiple endogenous biased ligands (Rajagopal et al, 2013). Synthetic biased agonists at GPR84 have been identified (Pillaiyar et al, 2017(Pillaiyar et al, , 2018Moghaddam et al, 2018), and recent work by Lucy et al (2019) has shown that G-protein-biased DL-175 has a diminished chemoattractant effect on human myeloid cells, while maintaining levels of phagocytosis enhancement.…”
Section: Multiple Physiological Ligandsmentioning
confidence: 99%
“…This is an exciting avenue to exploit for potential therapeutics (Kenakin, 2018), and the chemokine receptors are examples of immune-expressed GPCRs with multiple endogenous biased ligands (Rajagopal et al, 2013). Synthetic biased agonists at GPR84 have been identified (Pillaiyar et al, 2017(Pillaiyar et al, , 2018Moghaddam et al, 2018), and recent work by Lucy et al (2019) has shown that G-protein-biased DL-175 has a diminished chemoattractant effect on human myeloid cells, while maintaining levels of phagocytosis enhancement.…”
Section: Multiple Physiological Ligandsmentioning
confidence: 99%
“…strain 011, produced two cyclopropane-containing medium-chain fatty acids (1,2). Apart from inhibiting other bacteria, these compounds showed an inhibitory effect against strains of MDR MRSA LT-1338 and MRSA LT-1334 (2 and 3 mm) [38].…”
Section: Bacteria From Marine Sedimentsmentioning
confidence: 99%
“…showed activity against the oyster pathogen Roseovarius crassostreae [1]. R. crassostreae has an adverse effect on natural oyster populations and on oyster farming operations [5].…”
Section: Data Descriptionmentioning
confidence: 99%